Telegraphy and the downfall of the Kelly Gang: ? and other vignettes from the Telegraph Electrical Society of Victoria - Moorhead, Simon (Journal of Telecommunications and the Digital Economy, 2020)
Four historical vignettes are provided from the period 1875 to 1880 from the Proceedings of the Telegraph Electrical Society of Victoria ? the lineal antecedent of today’s TelSoc (Australian Telecommunications Society). The extracts cover Alexander Graham Bell’s invention of the telephone, Telegraphy at the downfall of the Kelly Gang, the speed of the Morse system, and the curious phenomenon of ‘Fighting by Telegraph’.